Thrown From the Train: Experiences that Contribute to the Spiritual Growth of Males in Mid-life - Dent C. Davis (Adult Education Research Conference, 2004)
This study of the spiritual experiences of an internationally and culturally diverse sample of eleven men identified a diverse expression of masculine spiritual experience involving transformations in awareness where the self moves from the role of subject to a growing sense of inter-subjectivity intimately related to the awareness of spirit.